2010
DOI: 10.1163/156853710x531186
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Moral Judgments are Robust across Variation in Gender, Education, Politics and Religion: A Large-Scale Web-Based Study

Abstract: Research on moral psychology has frequently appealed to three, apparently consistent patterns:(1) Males are more likely to engage in transgressions involving harm than females; (2) educated people are likely to be more thorough in their moral deliberations because they have better resources for rationally navigating and evaluating complex information; (3) political affiliations and religious ideologies are an important source of our moral principles. Here, we provide a test of how four factors -gender, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 43 publications
2
48
2
1
Order By: Relevance
“…On the other hand, similarities observed across cultures suggest the possibility of universal principles (Nisbett and Cohen, 1996;Gert, 2004;Henrich et aL, 2005Henrich et aL, ,2006Hauser, 2006;Haidt, 2007). For example, in two studies involving thousands of subjects tested on the internet, Häuser and colleagues (Häuser et al, 2007;Banerjee et al, 2010) found that religion, education, gender, political affiliation and age (among adults) played virtually no role in the pattern of Judgments, across a wide range of moral scenarios. These studies suggest that certain aspects of our moral psychology may be relatively immune to demographic and cultural factors.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, similarities observed across cultures suggest the possibility of universal principles (Nisbett and Cohen, 1996;Gert, 2004;Henrich et aL, 2005Henrich et aL, ,2006Hauser, 2006;Haidt, 2007). For example, in two studies involving thousands of subjects tested on the internet, Häuser and colleagues (Häuser et al, 2007;Banerjee et al, 2010) found that religion, education, gender, political affiliation and age (among adults) played virtually no role in the pattern of Judgments, across a wide range of moral scenarios. These studies suggest that certain aspects of our moral psychology may be relatively immune to demographic and cultural factors.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, empirical work has also confirmed the stability of intuition in the moral domain, with one recent large-scale study showing relatively little variation by gender, politics, religion and level of education (Banerjee, Huebner, and Hauser 2010).…”
Section: The Diversity Challengementioning
confidence: 88%
“…Some recent work shows that participants are slower and exhibit poor focus on the task while in scanner as opposed to the lab environment, though this difference was observed for a perceptual decision-making task93 and its relevance for social decision-making remains unclear. Future studies can also explore how variety of other demographic details94 (Big Five personality traits, education, ethnicity, etc.) and more realistic contexts95 affect moral judgments rather than relying primarily on a uniform group university students and hypothetical text vignettes as sampled in the current study.…”
Section: Discussionmentioning
confidence: 99%